MENTAL HEALTH, WELL-BEING AND THE USE OF HEALTHCARE SERVICES AMONG OLDER LATVIAN DIASPORA - Reine, Ieva; Koroļeva, Ilze; Goldmanis, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Mental health factors play a crucial role in the well-being pattern of migrants, and how the social security is being used. The aim of the study was to investigate, how the mobility across Europe and other regions of the world for different patterns and transnational lifestyles relate to mental health, wellbeing and healthcare as a pillar for social security and overall wellbeing. We analysed personal characteristics, including self-rated health and pre-disposing factors in order to reflect on the mental health differences for migrant groups.The study includes groups of 6242 respondents living outside Latvia who answered questions about their mental health as well as rated their overall health and assessed the use of the healthcare on a rotating basis in a 2019 survey “Research of Welfare and Social Integration in the Context of Liquid Migration: Longitudinal Approach”. Comprehensive data on migrants from many countries all over the world allowed to perform multiple regression analysis on stratified groups by migration patterns, including both individual and contextual level variables. Results of the analysis showed that older migrants tended to have less psychological symptoms compared to younger persons. Moreover, those who were born or had lived in another country seemed to be more confident in the use of healthcare system in the country of residence. The results showed that individual factors like age, gender, language of communication and education level are strongly related to the use of the healthcare system of the country of origin and better health.